2019
DOI: 10.3126/njb.v7i1.26944
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Profile of respiratory pathogens obtained at tertiary care hospital from western Nepal

Abstract: The prevalence and drug resistance of the respiratory pathogens is increasing gradually in Nepal. However, their detail study is rare in the western region of Nepal. Hence, this study was carried out to know the incidence and antibiotic susceptibility profile of the respiratory pathogens obtained at a tertiary care center located at Pokhara. 139 pathogens were isolated from 460 clinical samples included. Significant pathogens were Gram-negative bacteria 94 (67.62%), followed by 28 (20.15%) Candida, and Gram-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…1 Another study was done in Nepal also shows cultural positivity of 30.2% with gram-negative predominance. 10 In this study, Klebsiella pneumoniae (37.9%) was the most common isolate followed by ACB complex (29.3%). The other isolates included Escherichia coli, Pseudomonas aeruginosa, Citrobacter species, Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…1 Another study was done in Nepal also shows cultural positivity of 30.2% with gram-negative predominance. 10 In this study, Klebsiella pneumoniae (37.9%) was the most common isolate followed by ACB complex (29.3%). The other isolates included Escherichia coli, Pseudomonas aeruginosa, Citrobacter species, Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 61%
“…This is in concordance with another study that reported that gram-negative bacteria have a higher sensitivity to carbapenems. 10 High rate of resistance of the gramnegative isolates was observed towards ampicillin, cephalosporins, cotrimoxazole, and levofloxacin. The gram-negative isolates were resistant to most of the antibiotics tested.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation